Effect of Sex on Nadir Hematocrit and Rates of Acute Kidney Injury in Coronary Artery Bypass - Brescia, Alexander A. (J Thorac Cardiovasc Surg, 2019)
OBJECTIVE: Findings from a large multi-center experience showed that sex influenced the relationship between low nadir hematocrit (Hct) and increased risk of acute kidney injury (AKI) following cardiac surgery. We explored whether sex-related differences persisted among patients undergoing isolated coronary artery bypass grafting (CABG). METHODS: We undertook a prospective, observational study of 17,363 non-dialysis patients (13,137 male: 75.7%; 4,226 female: 24.3%) undergoing isolated CABG between 2011-2016 across 41 institutions in the Perfusion Measures and Outcomes registry. Odds ratios (OR) between nadir Hct and stage 2 or 3 AKI were calculated and the interaction of sex with nadir Hct was tested. The multivariable generalized linear mixed effect model adjusted for pre- and intra-operative factors and institution. RESULTS: Median nadir Hct was 22% among women and 27% among men (p<0.001). Women were administered a greater median net prime volume indexed to body surface area (407 ml/m2 vs. 363 ml/m2) and more red blood cell (RBC) transfusions (55.5% vs. 24.3%), both p<0.001. AKI was higher among women (6.0% vs. 4.3%, p<0.001). There was no effect of sex on the relationship between nadir Hct and AKI (p=0.67). Low nadir Hct was inversely associated with AKI (adjusted OR per 1-unit increase in nadir Hct 0.96, CI 95%: 0.93 to 0.98); this effect was similar across sexes and independent of RBC transfusions. CONCLUSIONS: We found no sex-related differences in the effect of nadir Hct on AKI following isolated CABG. However, the strong inverse relationship between anemia and AKI across sexes suggests the importance of reducing exposure to low nadir Hct.